2006
DOI: 10.1590/s1676-06032006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Turtles of the Tiputini Biodiversity Station with remarks on the diversity and distribution of the Testudines from Ecuador

Abstract: Cisneros-Heredia, D.F. Turtles of the Tiputini Biodiversity Station with remarks on the diversity and distribution of the Testudines from Ecuador. Biota Neotrop. Jan/Abr 2006, vol. 6, no. 1 http://www.biotaneotropica.org.br/v6n1/pt/ abstract?inventory+bn00906012006. ISSN 1676-0611 Ten species of Testudines, from four different families: Chelidae, Kinosternidae, Podocnemididae, and Testudinidae, are reported from the Tiputini Biodiversity Station (Universidad San Francisco de Quito), northeastern Amazonian Ecua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Illegal harvest of chelonians was reported to be particularly common along the Purus River (Kemenes and Pezzuti, 2007 Group, 1996;Bonin et al, 2006), and reported the species from eastern Ecuador. P. unifilis was observed in surveys conducted along the Tiputini river in the Orellana Province (eastern Ecuador) between (Cisneros-Heredia, 2006, and also along the Aguarico river basin (eastern Ecuador) (Townsend et al, 2005). It was not observed during a total of 1117 effort-hours of sampling during 1986-2007 at the Jatun Sacha reserve in eastern Ecuador (Vigle, 2008).…”
Section: Distribution In Range Statementioning
confidence: 97%
“…Illegal harvest of chelonians was reported to be particularly common along the Purus River (Kemenes and Pezzuti, 2007 Group, 1996;Bonin et al, 2006), and reported the species from eastern Ecuador. P. unifilis was observed in surveys conducted along the Tiputini river in the Orellana Province (eastern Ecuador) between (Cisneros-Heredia, 2006, and also along the Aguarico river basin (eastern Ecuador) (Townsend et al, 2005). It was not observed during a total of 1117 effort-hours of sampling during 1986-2007 at the Jatun Sacha reserve in eastern Ecuador (Vigle, 2008).…”
Section: Distribution In Range Statementioning
confidence: 97%
“…P. expansa is an explicit case of the fragility of the turtle populations in the Amazonian region. The extreme and uncontrolled overexploitation of this giant river turtle has reduced its numbers to the point that its long-term survivorship is uncertain [ 36 ]. Habitat alteration, pollution, human exploitation, diseases and introduced species are directly implied in the decline of several turtles species around the world [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could explain its great variety of helminths, principally those with direct life cycles. The yellow-spotted Amazon River turtle, P. unifilis is also a species that lives in a wide variety of habitats, such as rivers and lakes (Cisneros-Heredia, 2006). However, its helminth parasites have been poorly studied (Salizar & Sánchez, 2004;Sánchez et al, 2006;Tantaleán et al, 2011;Tantaleán & Forlong, 2013).…”
Section: Discussionmentioning
confidence: 99%